Optimasi Identitas Visual Empu Keris melalui Totem signage untuk Meningkatkan Daya Tarik Desa Wisata Keris Aeng Tong Tong Sumenep - Putra, Deni Fardiansyah; Hujairi, Ahmad Walid; Umam, Ahmad Khairul; Prasetyo, Joko; Hari, Nirwana Haidar; Agustien, Lusiana; Khoironi, Khoironi; Kurli, Anis (Jurnal SOLMA, 2025)
Background: Aeng Tong-Tong Village in Sumenep Regency is widely recognized as a center for traditional kris craftsmanship. It is the only area in Indonesia with the largest number of kris masters (Empu), with approximately 600 practitioners officially acknowledged by UNESCO. Despite this cultural richness, the village still lacks a well-developed visual identity and information system, particularly in aspects such as directional signage, visual branding, and overall appeal to tourists and visitors. This community engagement initiative aims to design, enhance, and implement a strong visual identity for the Empu Keris, serving both as a means of cultural preservation and promotional media. Method: Methodology: The activities were carried out through several stages, including workshops on preservation and conservation techniques, digital marketing and visual promotion training, and a cultural festival culminating in the official unveiling of totem signage. These efforts were specifically directed at Through a strategic and collaborative design process, the program successfully produced visual elements that function as distinctive markers, helping visitors easily identify the kris artisans and masters in Aeng Tong-Tong Village. Conclusion: The installation of kris-shaped totem signage in Aeng Tong-Tong serves as a meaningful step toward strengthening the villages visual identity as a cultural tourism destination, while actively preserving and honoring the ancestral heritage of the Indonesian archipelago.